Anxiety in health care workers who treated COVID-19 patients in hospitals in Tlaxcala, Mexico - Hernandez Vicente, Irma Alejandra; Méndez Hernández, Pablo; Lumbreras Delgado, Irma; Cerón Meza, Rosalba; Quiroz Campas, Celia Yaneth; Banderas Tarabay, José Antonio (Horizonte Sanitario, 2025)
Objective: To evaluate the presence of state-trait anxiety in health care workers who attended patients with COVID-19 in public hospitals in Tlaxcala, Mexico. Materials and Methods: A cross-sectional study with a convenience sample population of 245 health care workers from 3 general hospitals and 4 hospitals with specific areas to treat SAR-CoV-2 infected patients. Quantitative and multivariate analysis of the data was performed using the Mann-Whitney U and Chi-square test. Logistic regression models were used to evaluate the risk of trait-state anxiety. The information was collected through the State-Trait Anxiety Inventory. Results: The prevalence of trait-anxiety was 47.8% and state-anxiety was 85.7%. Temporary personnel were 1.9 times more likely to present moderate state anxiety and 2.15 times more likely to present severe state anxiety compared to the permanent staff. In terms of severe trait anxiety, participants in other work categories were 3.6 times more likely to present moderate anxiety and 11.4 times more likely to present severe anxiety status. No statistical differences were found between male and female personal.  Conclusion: There is a need to develop intervention and mental health promotion strategies for health professionals, especially during humanitarian and epidemiological risk emergencies. Long-term training and capacity-building should be performed frequently in all health institutions.  Key words: Health Personnel; Anxiety; COVID-19; SARS-CoV-2; Mexico.